The Sprout Regulating Compound 1,4-Dimethylnaphthalene Exhibits Fungistatic Activity - Michael Campbell; Rachael Adams; Emily Dobry; Kara Dobson; Veronica Stefanick; Jessica Till (Journal of Agronomy Research, 2019)
The compound 1,4-dimethylnaphthalene, originally isolated from dormant potatoes, is currently in use as a commercial sprout inhibitor. Growers and processors report a reduction in fungal infections in potatoes treated with DMN resulting in increased yields. To assess the effects of DMN on fungal growth a culture of Fusarium oxysporum was isolated from potato tubers and identified via DNA fingerprinting using the 18ITS ribosomal region. Growth of F. oxysporum was inhibited by 31% after four days of exposure to DMN but overall rate of spore germination was not affected by DMN treatment. The growth of additional fungi, including Alternaria alternata, Aspergillus niger, Epicoccum nigrum, Gnomoniopsis smithogilvyi, Phoma medicaginis, and Pythium ultimum was inhibited by DMN as was suppression of sporulation in A. niger. These results suggest that DMN is fungistatic at the application levels examined.
Keywords: 1; 4-Dimethylnaphthalene (DMN)